Metode Relaksasi Untuk Mengurangi Stres Pada Penderita Hipertensi Essensial - , Hanna Fatma Sari; , Dr. Murtini, SU., Psi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Patients with essential hypertension are susceptible to psychological problems including stress. The purpose of this study is to find out the effectiveness of relaxation therapy in reducing stress among patients with essential hypertension. Participants in the study were five patients with essential hypertension in moderate and high level of stress. Thi research used the adapted Depression Anxiety Stress Scales. An experimental design used the ABA small N. A therapy was given individually in seven sessions for four weeks. Quantitative analysis was done by using visual inspection to reveal the dynamic of stress scores among patients with essential hypertension. Qualitative analysis was done by analyzing results of interview, observation, and books on participant progress. Result of the studied indicates that relaxation therapy could reduce stress among patients with essential hypertension.